Laser-beam-triggered microcavitation: a novel method for selective cell destruction - Leszczynski, Dariusz; Pastila, Riikka K.; Pitsillides, Costas (My University, 2001)
We describe a new method of cell destruction that may have potential for use in antitumor therapy. Cells are loaded by phagocytosis with microparticles (<1 μm) and irradiated with short laser pulses. Absorption of laser energy by the microparticles causes localized vaporization of the fluid surrounding the microparticles, leading to the generation of transient vapor bubbles (microcavitation) around the microparticles. Using cultures of bovine aortic endothelial cells, we demonstrate that induction of intralysosomal microcavitation is an efficient, rapid and selective method of cell killing that is dependent on the number of microparticles, the number of laser pulses, and the fluence of the laser pulses. Cell killing by microcavitation is a very selective process that is restricted to cells containing microparticles, leaving other cells unaffected. Intracytoplasmic release of lysosomal hydrolases is, in part, responsible for cell death, because the protease inhibitors E64d and TLCK diminished cell killing. Using the broad-specificity caspase inhibitor Z-VAD-fmk, we determined that lysosomal hydrolases could induce apoptosis in a caspase-independent manner. We also examined the possibility of microcavitation-induced delayed effects in the cells that survived the treatment. Using flow cytometry, we determined that there was no delayed cell death between 1 and 4 days after microcavitation. Moreover, we did not observe changes in the cell cycle, in expression of the proteins BCL2, HSP70 and HSP27, or in PARP degradation. In conclusion, microcavitation induces rapid and specific cells death (limited only to cells containing microparticles), without producing delayed effects among the surviving cells
Keywords: Lasers; Cells; Apoptosis; Cell death; Endosomes; Cattle